2016
DOI: 10.1002/chem.201603060
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Acid–Base Properties of Binuclear 4‐Terphenyldithiophenolate Complexes of Nickel

Abstract: This work reports on the redox and acid–base properties of binuclear complexes of nickel from 1,4‐terphenyldithiophenol ligands. The results provide insight into the cooperative electronic interaction between a dinickel core and its ligand. Donor/acceptor contributions flexibly adjust to stabilize different redox states at the metals, which is relevant for redox reactions like proton reduction. Proton transfer to the [S2Ni2] core and Ni−H bond formation are kinetically favored over the thermodynamically favore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 96 publications
3
15
0
Order By: Relevance
“…As a starting point, the series of isostructural bimetallic cations L ‐[2Ni‐2S] + shown in Figure , with L =PMe 3 ( 1 ), PPh 3 ( 2 ), and P(Cy) 3 ( 3 ; Cy=C 6 H 11 ) was selected. The mixed‐valent [2Ni‐2S] + cores in this series feature aryl thiolate‐bridged tetrahedral nickel sites that are antiferromagnetically coupled to adopt an electron localized S= 1/2 ground state structure . Cyclic voltammetry (CV) at a glassy carbon working electrode in 0.1 m n Bu 4 NPF 6 /1,2‐C 6 H 4 F 2 solution at 23 °C has shown that oxidation of L ‐[2Ni‐2S] + to putatively isostructural L ‐[2Ni‐2S] 2+ is electrochemically reversible at potential sweep rates ν ≤5000 mV s −1 , irrespective of the type of phosphine donor .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a starting point, the series of isostructural bimetallic cations L ‐[2Ni‐2S] + shown in Figure , with L =PMe 3 ( 1 ), PPh 3 ( 2 ), and P(Cy) 3 ( 3 ; Cy=C 6 H 11 ) was selected. The mixed‐valent [2Ni‐2S] + cores in this series feature aryl thiolate‐bridged tetrahedral nickel sites that are antiferromagnetically coupled to adopt an electron localized S= 1/2 ground state structure . Cyclic voltammetry (CV) at a glassy carbon working electrode in 0.1 m n Bu 4 NPF 6 /1,2‐C 6 H 4 F 2 solution at 23 °C has shown that oxidation of L ‐[2Ni‐2S] + to putatively isostructural L ‐[2Ni‐2S] 2+ is electrochemically reversible at potential sweep rates ν ≤5000 mV s −1 , irrespective of the type of phosphine donor .…”
Section: Resultsmentioning
confidence: 99%
“…The mixed‐valent [2Ni‐2S] + cores in this series feature aryl thiolate‐bridged tetrahedral nickel sites that are antiferromagnetically coupled to adopt an electron localized S= 1/2 ground state structure . Cyclic voltammetry (CV) at a glassy carbon working electrode in 0.1 m n Bu 4 NPF 6 /1,2‐C 6 H 4 F 2 solution at 23 °C has shown that oxidation of L ‐[2Ni‐2S] + to putatively isostructural L ‐[2Ni‐2S] 2+ is electrochemically reversible at potential sweep rates ν ≤5000 mV s −1 , irrespective of the type of phosphine donor . Preparative scale oxidation of the three complexes L ‐[2Ni‐2S] + by using the 1,1′‐bisacetylferrocene cation in 1,2‐C 6 H 4 F 2 solution affords two structurally isomeric products, depending on the type of phosphine donor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations